Validation of a rapid SARS-CoV-2 antibody test in general practice - Herman Goossens; Ann Van den Bruel; Beatrice Scholtes; An De Sutter; Jan Yvan Jos Verbakel; Laetitia Buret; Pierre Van Damme; Samuel Coenen; Robin Bruyndonckx; Els Duysburgh; Stefan Heytens; Niels Adriaenssens; et al. (BMJ Open, 2023)
Objectives To validate a rapid serological test (RST) for SARS-CoV-2 antibodies used in seroprevalence studies in healthcare providers, including primary healthcare providers (PHCPs) in Belgium.Design A phase III validation study of the RST (OrientGene) within a prospective cohort study.Setting Primary care in Belgium.Participants Any general practitioner (GP) working in primary care in Belgium and any other PHCP from the same GP practice who physically manages patients were eligible in the seroprevalence study. For the validation study, all participants who tested positive (376) on the RST at the first testing timepoint (T1) and a random sample of those who tested negative (790) and unclear (24) were included.Intervention At T2, 4 weeks later, PHCPs performed the RST with fingerprick blood (index test) immediately after providing a serum sample to be analysed for the presence of SARS-CoV-2 immunoglobulin G antibodies using a two-out-of-three assay (reference test).Primary and secondary outcome measures The RST accuracy was estimated using inverse probability weighting to correct for missing reference test data, and considering unclear RST results as negative for the sensitivity and positive for the specificity. Using these conservative estimates, the true seroprevalence was estimated both for T2 and RST-based prevalence values found in a cohort study with PHCPs in Belgium.Results 1073 paired tests (403 positive on the reference test) were included. A sensitivity of 73% (a specificity of 92%) was found considering unclear RST results as negative (positive). For an RST-based prevalence at T1 (13.9), T2 (24.9) and T7 (70.21), the true prevalence was estimated to be 9.1%, 25.9% and 95.7%, respectively.Conclusion The RST sensitivity (73%) and specificity (92%) make an RST-based seroprevalence below (above) 23% overestimate (underestimate) the true seroprevalence.Trial registration number NCT04779424.